2019
DOI: 10.3390/cryst9070332
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of Layered Titanium Phosphate Ti2O2H(PO4)[(NH4)2PO4]2 and Its Potential Application in Cosmetics

Abstract: Titanium phosphates were recently revealed as promising cosmetic pigments; however, their photocatalytic activity and sun protective factor (SPF) levels have not been investigated in detail. In this study, we used hydrothermal conditions to prepare nanocrystalline anatase, brookite, and layered titanium phosphate using the titanium lactate complex, NH4H2PO4, and urea as precursors. The samples were characterized by powder X-ray diffraction (XRD) in addition to Raman spectroscopy, transmission and scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…For example, for Ce III PO 4 (rhabdophane), the value of E g calculated by Lima et al was 2.7-2.8 eV, 56 for Ce(PO 4 )(HPO 4 ) 0.5 (H 2 O) 0.5 it was 2.7 eV 64 and for amorphous cerium pyrophosphate it was 2.3 eV. 61 The values of the energy band gap obtained in the current study are consistent with the literature data and indicate the 54 2.7 2.5 0.9 3.2 TiO 2 (rutile) 54 3.1 3.1 1.0 3.0 possibility of using cerium(IV) phosphates as components of UV protective materials: Cole et al, 75 using the example of zinc and titanium oxides (inorganic sunscreens approved by the FDA, E g = 3.1-3.3 eV 76 ), showed that metal oxide sunscreens protect skin by light absorption, not by reflection or scattering, with absorption efficiency being associated with the semiconductor band gap. At wavelengths above the semiconductor band gap absorption energy levels (in the long-wavelength UV-A and visible range), semiconductor nanoparticles predominantly reflect (up to 60% reflection), and do not absorb, radiation.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…For example, for Ce III PO 4 (rhabdophane), the value of E g calculated by Lima et al was 2.7-2.8 eV, 56 for Ce(PO 4 )(HPO 4 ) 0.5 (H 2 O) 0.5 it was 2.7 eV 64 and for amorphous cerium pyrophosphate it was 2.3 eV. 61 The values of the energy band gap obtained in the current study are consistent with the literature data and indicate the 54 2.7 2.5 0.9 3.2 TiO 2 (rutile) 54 3.1 3.1 1.0 3.0 possibility of using cerium(IV) phosphates as components of UV protective materials: Cole et al, 75 using the example of zinc and titanium oxides (inorganic sunscreens approved by the FDA, E g = 3.1-3.3 eV 76 ), showed that metal oxide sunscreens protect skin by light absorption, not by reflection or scattering, with absorption efficiency being associated with the semiconductor band gap. At wavelengths above the semiconductor band gap absorption energy levels (in the long-wavelength UV-A and visible range), semiconductor nanoparticles predominantly reflect (up to 60% reflection), and do not absorb, radiation.…”
Section: Resultssupporting
confidence: 90%
“…To determine the optical band gap ( E g ) of cerium( iv ) phosphates, the absorption spectra of their powders were recorded (see Fig. S1, ESI†) and the data were processed using the Kubelka–Munk equation: 54 where R is reflection. Since it is not reliably known what type of transition is realised in the substances under study, for the indirect transition the graph of ( F·hν ) 1/2 was analysed as a function of hν , and for the direct transition the graph of ( F·hν ) 2 was analysed as a function of hν (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…P-Ti 3 C 2 -An-PA@1 : 10 showed multiple peaks at different positions, which correspond to various Ti-O and P-O vibrations related to phosphates as evidenced by previous studies on titanium phosphates. 57,58 Therefore, aer the Raman analysis, it can be further conrmed that the formation of titanium phosphate free P-Ti 3 C 2 prefers MW heating over conventional heating.…”
Section: Resultsmentioning
confidence: 99%